RDTs as a source of DNA to study Plasmodium falciparum drug resistance in isolates from Senegal and the Comoros Islands. (December 2015) - Papa Mze, Nasserdine; Ndiaye, Yaye; Diedhiou, Cyrille; Rahamatou, Silai; Dieye, Baba; Daniels, Rachel; Hamilton, Elizabeth; Diallo, Mouhamadou; Bei, Amy; Wirth, Dyann; Mboup, Souleymane; Volkman, Sarah; et al.
Abstract Background The World Health Organization has recommended rapid diagnostic tests (RDTs) for use in the diagnosis of suspected malaria cases. In addition to providing quick and accurate detection ofPlasmodium parasite proteins in the blood, these tests can be used as sources of DNA for further genetic studies. As sulfadoxine-pyrimethamine is used currently for intermittent presumptive treatment of pregnant women in both Senegal and in the Comoros Islands, resistance mutations in thedhfr anddhps genes were investigated using DNA extracted from RDTs. Methods The proximal portion of the nitrocellulose membrane of discarded RDTs was used for DNA extraction. This genomic DNA was amplified using HRM to genotype the molecular markers involved in resistance to sulfadoxine-pyrimethamine:dhfr (51, 59, 108, and 164) anddhps (436, 437, 540, 581, and 613). Additionally, themsp1 andmsp2 genes were amplified to determine the average clonality between Grande-Comore (Comoros) and Thiès (Senegal). Results A total of 201 samples were successfully genotyped at all codons by HRM; whereas, in 200msp1 andmsp2 genes were successfully amplified and genotyped by nested PCR. A high prevalence of resistance mutations were observed in thedhfr gene at codons 51, 59, and 108 as well as in thedhps gene at codons 437 and 436. A novel mutant indhps at codon positions 436Y/437A was observed. Thedhfr I164L codon anddhps K540 anddhps A581G codons had 100 % wild type alleles in all samples. Conclusion The utility of field-collected RDTs was validated as a source of DNA for genetic studies interrogating frequencies of drug resistance mutations, using two different molecular methods (PCR and High Resolution Melting). RDTs should not be discarded after use as they can be a valuable source of DNA for genetic and epidemiological studies in sites where filter paper or venous blood collected samples are nonexistent.